Pengembangan Media Pembelajaran Interaktif Pada Mata Kuliah Pancasila Di Perguruan Tinggi - Nur Ikchsan; Siti Kholifah (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2023)
The post-Covid-19 pandemic period means that learning must be done online and offline from one's place so as not to immediately leave online learning. Teacher creativity in utilizing information and communication technology is important in compiling learning materials and media. However, the availability of tools and supporting facilities is an obstacle. One of them is the internet network which is different in each region. Therefore, it is necessary to design learning media that does not require much internet access and can be accessed from each student's device. In this research, the initial stages of Pancasila learning media will be developed. The choice of Pancasila material as material aims to instill a Pancasila spirit in all students at Muhammadiyah Kudus University and STEKOM University Semarang. This research uses research and development research methods which are carried out up to step 5. This research involves teachers, academics and practitioners as media and material experts. The software used is flash software whose products can be accessed via a device. The results of the research are that an initial draft of the product has been produced which has been validated and tested on a limited basis with valid results and can be used in small-scale trials on campus.